PROMOTING AND PRESERVING MARGINALISED LANGUAGES IN MULTILINGUAL SOCIETIES IN AFRICA - Billy James Chavalala (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This article examined the sociolinguistic processes shaping the promotion and preservation of marginalised languages in multilingual societies in Africa, with particular focus on a linguistically diverse South African community. It investigated how social identity, community participation, and cultural contexts influenced language maintenance, intergenerational transmission, and revitalisation. Adopting a mixed-methods ethnographic design, the study combined sociolinguistic surveys with in-depth interviews among speakers from varied demographic and socioeconomic backgrounds to assess how identity, social class, age, gender, and motivation affected language practices and attitudes. The analysis further explored how speakers navigated sociocultural boundaries within complex multilingual networks and how dominant language ideologies shaped perceptions of legitimacy and value. Findings revealed that strong and dense social networks, especially regular interaction within family, peers, and community domains were the most significant predictors of language vitality and continued use. Participants embedded in supportive networks demonstrated greater linguistic engagement, cultural affiliation, and active transmission practices. Positive attitudes and linguistic pride strengthened preservation efforts, while stigma, limited institutional support, and restricted access to education and public domains accelerated language shift. Overall, the study showed that language sustainability depended not only on individual choices but also on broader social and structural conditions. It recommended inclusive language policies, community-based initiatives, and expanded opportunities for meaningful language use to enhance linguistic diversity and safeguard endangered African languages.Keywords: marginalised languages; language maintenance; language revitalisation; language policy; social networks; sociolinguistics; multilingualism.